Biogasoline synthesis through fluid catalytic cracking of rubber seed oil– effects of cracking temperature - Norsafiah, Fazli (2017)
Biogasoline generally can be produced from the fluid catalytic cracking process of vegetable oils, including rubber seed oil which is the alternative of gasolines sources that overcome the depletion of fossil fuel. Rubber seed oil has been converted into biodiesel in the previous research. However, biodiesel is only limited to diesel engines. Therefore, this research aims to focus on the effects of cracking temperature of the rubber seed oil in the biogasoline production via fluid catalytic cracking process to fulfil the biogasoline demand. The experiment in this research is being conducted by using laboratory-scaled set-up fluid catalytic cracking method. Through this method, the rubber seed oil is vaporized, condensed and collected in the attached Dean Stark trap. This method provides an easy-handling and easy-monitoring experiment as well as producing yield at sufficient amount. Zeolite ZSM-5 is selected as the catalyst used in this method due to its thermal stability and good shape-selective properties. The optimum cracking temperature of the fluid catalytic cracking of rubber seed oil was investigated by varying the temperature within 250˚C to 400 ˚C with fixed masses of catalyst and rubber seed oil. Also, the reaction time of the experiment are varied in the range of 1 to 10 minutes. The liquid product of the experiment will then be analysed by using the gas chromatography analysis which provides information regarding the gasoline fraction in the liquid product. From these results, optimization of the temperature and reaction time of fluid catalytic cracking of rubber seed oil in biogasoline synthesis is determined. The yield of the biogasoline is expected to increase as the temperature goes higher due to quantity of molecules being cracked increases as heat is supplied. The heating energy supplied will crack the chain of the rubber seed oil. However, the temperature limit is set to be at 400˚C as it is expected that the reaction rate will decrease beyond this temperature due to changes of the catalyst structure caused by the breaking link within the catalyst. Therefore, the optimization of cracking temperature can be determined based on biogasoline yield obtained. The optimized temperature will provide optimum biogasoline yield. Thus, the optimum condition of the fluid catalytic cracking process can be improved. This will contribute in increasing the production capacity of the biogasoline that will allow the substitution of the biogasoline in the gasoline usage to be fulfilled.